Persepsi Siswi SMAN Tanjungsari Terhadap Pencegahan Primer Penyakit Kanker Serviks - Sontiva, Nessa; Rahayuwati, Laili; Lukman, Mamat (Universitas 'Aisyiyah Bandung, 2019)
Cervical cancer was a disease that happen in many women. Prevalence of cervical cancer was high. Therefore, it is necessary to prevalence of cervical cancer. However, the cervical cancer prevention behavior was still low. One of the factors which affected it was the perception of primary prevention of cervical cancer. Early sexual intercourse behavior was one of the risk factors of cervical cancer, especially in teen age. This study aimed to determine the perception of senior high school woman about the primary prevention of cervical cancer disease. This research was a quantitative descriptive study. Using the stratified random sampling technique. This research was conducted at Tanjungsari senior higth school female. This stud involved 216 female student at that school. The data were collected using a questionnaire with Likert scale. The questionnaire contents included perceptions susceptibility, seriousness, benefits, and barriers. The instrument validity was 0,367 – 0,717 and the reliability was 0,811. The results showed that SMAN Tanjungsari students mostly had negative perception about susceptibility of cervical cancer (94,9%), positive perception toward cervical cancer seriousness (94%), positive perception toward primary prevention benefit of cervical cancer (98,6% ), and positive perceptions of primary prevention barrier of cervical cancer (96.8%). The conclusion of this research was the majority of student of SMAN Tanjungsari have positive perception toward primari prevention of cervical cancer disease. Based on these results, health services and educational institutions might develop establish a program o cervical cancer prevention that eas to acces by all student. So it will be a supporting factor for high school female to make efforts to prevent cervical cancer.